Serious games in management education: An acceptance analysis - Rodríguez López, Fernando; Arias-Oliva, Mario; Pelegrín-Borondo, Jorge; Marín-Vinuesa, Luz María (My University, 2022)
Training is a key resource for fostering knowledge as a competitive asset. As in other fields, in learning, innovation emerges with disruptive methods such as gamification. Serious games are a proven efficient training method based on the incorporation of traditional elements of games, such as entertainment, into learning. But as with any other innovation, people must be willing to use the new method. The use of even a proven serious game will not have any positive effect if students do not accept it. It is thus essential to analyze the intention to use serious games in management training contexts. This research uses an adapted CAN (Cognitive-Affective-Normative) model to explore the intention to use a serious game – Lego© Serious Play© – in a sample of higher-education students in their capacity as future professionals. The results show that the most critical factor influencing the intention to use serious games is expected learning performance. The proposed model opens a new methodology for studying the behavioral intention to use other innovative management-training methods and to enrich the deployment of serious game training strategies in management education.
Keywords: gamification; innovation; knowledge; serious games; training and development; Scopus; JCR